Groundwater pollution in the city of Zahedan, Eastern Iran - Lashkaripour, G. R. (Journal of Nepal Geological Society, 2000)
Zahedan, with a population of about 500,000, lies in the most arid area of Eastern Iran, close to Pakistan border. This city has shown the highest rate of population grown among the big cities of the country in the last two decades. Groundwater is the sole water source for the city. It is provided from an aquifer with an area of 120 km2. Groundwater pollution and problems in water supply appear to be the main factors preventing the sustainable economic development of the city . The quality of groundwater has deteriorated sharply since last several years owing to the following main factors. (1) Groundwater pumping has exceeded natural recharge in the Zahedan watershed since 1980, and groundwater level in the city has been declining because of low yearly rainfall (Precipitation in the Zahedan watershed averages 95 mm per year, mainly in the winter). (2) The city population is growing fast, especially after 1980, and the aquifer pollution by human activities is serious. (3) Uncontrolled and unplanned development of the city in the western part over the aquifer that is providing fresh water has led to the problem of overexploitation and further groundwater pollution . At present, a massive federal project for the construction of 191 km long pipeline is in progress. It will fulfill the public demand of drinking water by bringing water from the Chahnimah Reservoir that is fed by the Hirmand River.